Bile Acids Increase Independently From Hypocaloric Restriction After Bariatric Surgery. Issue 6 (December 2016) - Jahansouz, Cyrus; Xu, Hongliang; Hertzel, Ann V.; Serrot, Federico J.; Kvalheim, Nicholas; Cole, Abigail; Abraham, Anasooya; Luthra, Girish; Ewing, Kristin; Leslie, Daniel B.; Bernlohr, David A.; Ikramuddin, Sayeed
Abstract : Objectives: To measure changes in the composition of serum bile acids (BA) and the expression of Takeda G-protein-coupled receptor 5 (TGR5) acutely after bariatric surgery or caloric restriction. Summary Background Data: Metabolic improvement after bariatric surgery occurs before substantial weight loss. BA are important metabolic regulators acting through the farnesoid X receptor and TGR5 receptor. The acute effects of surgery on BA and the TGR5 receptor in subcutaneous white adipose tissue (WAT) are unknown. Methods: A total of 27 obese patients with type 2 diabetes mellitus were randomized to Roux-en-Y gastric bypass (RYGB) or to hypocaloric diet (HC diet) restriction (NCT 1882036). A cohort of obese patients with and without type 2 diabetes mellitus undergoing vertical sleeve gastrectomy was also recruited (n = 12) as a comparison. Results: After vertical sleeve gastrectomy, the level of BA increased [total: 1.17 ± 1.56 μmol/L to 4.42 ± 3.92 μmol/L ( P = 0.005); conjugated BA levels increased from 0.99 ± 1.42 μmol/L to 3.59 ± 3.70 μmol/L ( P = 0.01) and unconjugated BA levels increased from 0.18 ± 0.24 μmol/L to 0.83 ± 0.70 μmol/L ( P = 0.009)]. With RYGB, there was a trend toward increased BA [total: 1.37 ± 0.97 μmol/L to 3.26 ± 3.01 μmol/L ( P = 0.07); conjugated: 1.06 ± 0.81 μmol/L to 2.99 ± 3.02 μmol/L ( P = 0.06)]. After HC diet, the level of unconjugated BA decreased [0.92 ± 0.55 μmol/L to 0.32 ± 0.43 μmol/L ( P = 0.05)]. The level of WAT TGR5 gene expression decreased after surgery, but not in HC diet. Protein levels did not change. Conclusions: The levels of serum BA increase after bariatric surgery independently from caloric restriction, whereas the level of WAT TGR5 protein is unaffected.